Revestimento a base de galactomanano de sementes de Jucá (Libidibia ferrea) adicionado de micropartículas de ácido ascórbico e sua aplicação em melão minimamente processado. - Aragão, Marília de Freitas Cabral (2018)
Edible coatings are an interesting option for preservation of minimally processed fruits, and some materials as polysaccharides are used due to their ability to gel in an aqueous medium. Thus, the galactomannans is polysaccharide employed in industries due to control water activity, stabilize solutions and aqueous dispersions, i.e., act as thickener. The Libidibia ferrea is a legume in which the galactomannan is present in the endosperm. Another feature about edible coating is the availability of ascorbic acid, which is stable in the powder form. However, this characteristic decreases when dissolved in water. In order to correct this deficiency, the encapsulation technique by spray drying is the most appropriate and currently used method. The Melon (Cucumis melo L.) is a highly appreciated fruit due to its attractive sensory characteristics, but minimally processed melon is highly susceptible to softening during storage, even under refrigerated conditions. Thus, this work aims to prepare L-ascorbic acid microparticles in galactomannan obtained from L. ferrea seeds by the spray drying technique, as well as evaluate the edible coating of galactomannan added ascorbic acid microparticles on the quality, antioxidant potential and structure in minimally processed melon. The microparticles were obtained in 5: 1 and 10: 1 proportions (galactomannan: ascorbic acid) and analyzed as for encapsulation efficiency and total antioxidant activity. The results showed that the microparticles had lower total antioxidant activity when compared to the non-encapsulated ones. The 10:1 proportion showed a higher encapsulation efficiency (59.6%) and, therefore, this proportion was selected for application in coated melons, as well as the characterization of these microparticles. The analyzes measured were weight loss, color, soluble solids, pH, acidity, vitamin C, carotenoids, flavonoids, polyphenols, total antioxidant activity, firmness, lipid peroxidation, activity of polygalacturonase enzymes and pectinamethylesterase and its microstructure for 12 days at 10 °C. The control and galactomannan-coated samples were able for consumption only for nine days due to fungal growth, while the microparticles coating resulted in extended shelf life of coated melons up to twelve days.